Cellular Mechanics and Therapeutic Resistance of the Cancer Relapse - Emad, Y. Moawad (Journal of Radiation and Nuclear Medicine, 2017)
The aims of this study are to investigate the variation in the mechanical behaviour of the primary cancer from cancer relapse, and measuring the therapeutic resistance acquired by cancer relapse. A431-cultured cells were irradiated for 7 months until 85 Gy. Then, a selected single cell was left to grow as stable A431-R cell line. 106 cells of A431 cells and 106 of A431-R cells suspended in 100 μL of medium were injected into subcutaneous tissues on the right thigh of athymic mice to generate tumor xenografts models of primary cancer (A431-P) and cancer relapse (A431-R). Radiotherapy of a low-dose of 30Gy was applied on xenoimplanted tumors after one week from inoculation. A mock process was performed on untreated groups of mice for controls. Tumor size was monitored starting from inoculation and tumor growth was measured along 42 days. Rates of mitosis and apoptosis and the histologic grade (HG) that characterize the tumor response were determined as described in earlier studies. Alterations induced on tumor HG in the treated models were 100% identical to the energy of the applied doses. The differences in response energy between cancer relapse and primary cancer irrespectively of the treatment (untreated vs. treated) or origin of the cells (A431-P vs. A431-R) in all phases of tumor responses (growth, shrinkage or regrowth) were 100% identical to the total differences in the administered regimens applied on those groups during those phases. Cancer relapse is characterized by a delay in growth before second line therapy for its relatively lower rate of mitosis compared by the primary cancer inducing a corresponding delay in the early detection. The therapeutic resistance of the cancer relapse is equivalent to the energy of the doses which have been delivered in the prior therapies, and requires increasing the administered dose by an amount equivalent to that resistance.
Keywords: Cancer relapse; Primary cancer; Histologic grade; Mitosis; Apoptosis.